Anisodamine hydrobromide attenuates oxidative stress and proinflammatory cytokines in septic rats induced by cecal ligation and puncture: Role of Ani HBr in protecting against septic injury - Qiu, Yan; Ouyang, Zhi; Zhong, Jian; Shen, Junyi; Jiang, Wenli; Liu, Yan; Wan, Feng; Zeng, Ye (Cellular and Molecular Biology, 2022)
We previously demonstrated that anisodamine hydrobromide (Ani HBr) ameliorates septic organ injury induced by lipopolysaccharide. The present study is aimed to explore the role of Ani HBr in protecting the organs against inflammation and oxidative stress in septic rats induced by cecal ligation and puncture. A total of forty-two rats were randomly divided into sham (sham operation), septic shock, Ani HBr, atropine, and racemic anisodamine (Rac Ani) groups. Ani HBr (1.8, 3.6, and 5.4 mg/kg), atropine (5.4 mg/kg), and Rac Ani (5.4 mg/kg) were administrated to septic rats. After 24 h, the plasma and organs including brain, heart, liver, lung, kidney, and intestine were obtained. Then, the H&E staining and TUNEL staining were performed. The proinflammatory factors TNF-α and IL-6 and oxidative stress markers superoxide dismutase (SOD) and malondialdehyde (MDA)in plasma were detected by ELISA. H&E staining showed that the tissues in the brain, heart, liver, lung, kidney, and intestine in the septic shock group were seriously damaged. Consistently, TUNEL staining showed an increase of apoptotic cells in those tissues. Ani HBr treatment alleviated the injury and apoptotic cells in all those organs in septic rats. Ani HBr, atropine, and Rac Ani reduced the plasma TNF-α and IL-6 levels in septic rats, whereas 5.4 mg/kg Ani HBr reduced the cytokines more than Rac Ani. Ani HBr raised SOD activity and reduced plasma MDA levels in a concentration-dependent manner, which at 5.4 mg/kg were greater than atropine and Rac Ani. Therefore, anisodamine hydrobromide suppressed the proinflammatory cytokines and oxidative stress, thereby alleviating organ injury in rats with septic shock. Moreover, the therapeutic effect of Ani HBr is more powerful than that of atropine or Rac Ani, which suggests that Ani HBr is a preferred treatment for septic shock.